About the current situation with regard to the risks and prevention of venous thromboembolic complications after varicose vein surgery - V. Yu. Bogachev; K. V. Lobastov; A. A. Fokin; E. V. Shaydakov; E. P. Burleva; A. Yu. Krylov; V. E. Barinov; S. M. Belentsov; V. V. Soroka; R. A. Bredikhin; D. A. Rosukhovski; D. A. Borsuk; et al. (Амбулаторная хирургия, 2022)
.